Advantages and Prospects of E-Commerce in the Context of Green Economy Development (KIUT Publication, 2025)
The green economy is an economic model shaped by the principles of natural resource conservation, ecological sustainability, and the use of renewable energy sources. According to the UN, the transition to a green economy is expected to increase global green investments to $2.5 trillion by 2030. Its main principles include the protection of natural capital (reforestation, water conservation), the transition to clean energy (utilization of solar and wind energy), and sustainable production (minimization of waste).